2013
DOI: 10.1037/a0033682
|View full text |Cite
|
Sign up to set email alerts
|

High and low roads to odor valence? A choice response-time study.

Abstract: Valence and edibility are two important features of olfactory perception, but it remains unclear how they are read out from an olfactory input. For a given odor object (e.g., the smell of rose or garlic), does perceptual identification of that object necessarily precede retrieval of information about its valence and edibility, or alternatively, are these processes independent? In the present study, we studied rapid, binary perceptual decisions regarding odor detection, object identity, valence, and edibility f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 39 publications
1
33
1
Order By: Relevance
“…A recent study suggested that when rapid behavioral responses were based on accessing the valence of a familiar odor, decision latencies were consistently longer (> 100 ms) and more variable compared to an object categorization task [29]. Similar results were obtained in a follow-up study where odors were subject to binary classifications based on their valence or object properties [30]. These findings suggest, at least for familiar smells, that odor objects manifest early in the processing stream [31].…”
Section: Behavioral and Perceptual Insights Into Odor Perception And mentioning
confidence: 59%
“…A recent study suggested that when rapid behavioral responses were based on accessing the valence of a familiar odor, decision latencies were consistently longer (> 100 ms) and more variable compared to an object categorization task [29]. Similar results were obtained in a follow-up study where odors were subject to binary classifications based on their valence or object properties [30]. These findings suggest, at least for familiar smells, that odor objects manifest early in the processing stream [31].…”
Section: Behavioral and Perceptual Insights Into Odor Perception And mentioning
confidence: 59%
“…Pomp et al (2018) suggest the lack of piriform activation is due to the overall hedonicity of the olfactory sentences-which highlight a pleasant or unpleasant odour experience-and therefore activate secondary olfactory regions where odour valence is processed. However, since valence is thought to be the primary dimension by which odours are encoded (Khan et al, 2007;Yeshurun & Sobel, 2010;Zarzo, 2008;although see Olofsson et al, 2012;Olofsson, Bowman, & Gottfried, 2013), and odour language is also strongly encoded along this dimension (Levinson & Majid, 2014;Winter, 2016;Wnuk & Majid, 2014) piriform activation ought to be expected on a fully grounded perspective.…”
Section: Olfactionmentioning
confidence: 99%
“…However, competing research indicates that humans more likely identify the perceived identity of an odor in terms of its odorous quality (i.e. what it smells like) (Olofsson et al, 2012(Olofsson et al, , 2013. Additionally, Kumar et al (2015) created an alternative computational model to that of Snitz et al (2013) using descriptors of odor qualities and not judgements of valence, as well as measures of chemical structures to predict olfactory quality.…”
Section: Introductionmentioning
confidence: 99%